Pengaruh Lingkungan Kerja Dan Beban Kerja Terhadap Produktivitas Kerja Pegawai Medis Pada UPT Puskesmas Tanjungjaya - Ajeng Intan Mahmudah; Barin Barlian; Nita Fauziah Oktaviani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the Effect of Work Environment and Workload on the Work Productivity of UPT Medical Employees of Tanjungjaya Health Center. This study used quantitative method. The population in this study was 49 medical employees of UPT Puskesmas Tanjungjaya. The sampling technique in this study was saturated sampling of 49 people. Data analysis in this study used multiple linear analysis with SPSS program version 25. The results of this study show that the Work Environment and Workload simultaneously have a significant influence on the Work Productivity of UPT Puskesmas Tanjungjaya Medical Employees. The Work Environment partially has a significant influence on the Work Productivity of Medical Workers UPT Puskesmas Tanjungjaya. The workload partially has a significant influence on the work productivity of UPT Puskesmas Tanjungjaya Medical Employees.